Evaluation of the Transboundary Aquifer Agreements from the WEFE Nexus perspective - Ramos, Silmara Juliana de Oliveira (2025)
Purpose: Recognizing the holistic perspective that encompasses the interconnections between water,energy, food, and ecosystems, it becomes important to highlight the discussion about aquifer studiesintegrating the concepts of WEFE Nexus. Considering that the management of transboundary aquifersrelies on agreements signed between countries, it is relevant to investigate this topic by including it inthe framework of the WEFE Nexus. In this regard, the objective of this study is to understand how thewater-energy-food-ecosystem Nexus context is addressed in transboundary aquifer agreements.Methodology: The study adopted a qualitative approach, developing a core concept for the WEFE Nexus,composed of five analytical perspectives. This framework was developed through a systematic reviewof the literature based on SCOPUS and Web of Science databases. Transboundary aquifer agreementswere subsequently analyzed according to each analytical perspective, facilitating the identification ofkey issues, gaps, and opportunities in alignment with the WEFE Nexus context.Findings: We noted that none of the agreements fulfilled all the created perspectives. None ofthe agreements included data illustrating synergy among water, energy, food, and ecosystemresources, nor did they provide guidelines concerning the trade-offs among these resources. Thereare opportunities to enhance agreements and advance the objectives of the WEFE Nexus throughimprovements in Monitoring, Stakeholders, and Governance perspectives.Originality/value: The WEFE Nexus approach seeks to achieve a better balance in the use of naturalresources essential for human well-being. However, technical improvements are necessary withinthe agreements, taking into account the individual characteristics and requirements of each aquiferwithin the context of the WEFE Nexus. Finally, the primary contributions of the research are associatedwith providing a fresh approach and perspective to the discourse surrounding the management andgovernance of transboundary aquifers. In this regard, it extends beyond the scope of water alone andencompasses the other interconnected resources within this context.